Balinese peasants’ resistance in two short stories tahun baru di sawah bapak and pura subak (an analysis of ecocriticism) - Yanuaresti Kusuma Wardhani; Budi Susanto (Politeknik Negeri Bali, 2023)
Tourism is the most beneficial sector in Bali, Indonesia. Either domestic or foreign tourists visit Bali to enjoy its beauty and unique culture. Tourism in Bali is based on society, nature, and culture. One of the interesting tourist attractions comes from Bali’s amazing nature. To accommodate nature-based tourism, many hotels, villas, and resorts are built. It requires a broad area, and sometimes land conversion from the agricultural sector into the tourism sector happened. The phenomenon of agricultural land conversion is reflected in two stories Tahun Baru di Sawah Bapak and Pura Subak. The analysis is about the main characters who are peasants. They do resistance and fight against land conversion. Both stories are analyzed using the theory of ecocriticism. The research method uses qualitative research. The result of the analysis is that conversion is not suitable with the Balinese value, Tri Hita Karana. The analysis ends up with similarities and differences between the two stories. Those conclude that land conversion which happened in holy areas may trigger problems. Nevertheless, it has been happening since a long time ago and still going on.